Stylistic Conventions and Complex Group Collaboration - Marc Slors (Philosophies, 2025)
Social etiquette, dress codes and culture-specific architectural features are undoubtedly stylistic conventions. Literature from anthropology, sociology and ecological psychology suggests a coordinative function of such conventions, without, however, offering a theoretical analysis of this function. The best-known philosophical theory of conventions—by David Lewis—does offer a theoretical analysis of the coordinative function of conventions, but stylistic conventions typically fall outside the purview of this theory. The present paper suggests a remedy for this situation by putting to use the notion of ‘correlation devices’, developed as an addition to the Lewisian framework. I argue that stylistic conventions function as markers for social categories without which these categories become cognitively intractable. Given that social categories are a precondition for complex coordinated role-divisions, and given that such role-divisions are a major part of the explanation for our evolutionary success, I argue that it is likely that the psychological proclivities that make us susceptible to stylistic conventions can be explained as the result of group-level selection pressures.